Development of Ludo-Science Media with a Somatic Auditory Visual Intellectual (SAVI) Approach to Train the Activeness and Conceptual Understanding - Anggreini, Ramadhani Kasih; Dewi, Novi Ratna (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
This study is aimed to develop an educational game media called ludo-science that is compiled with Somatic Auditory Visualization Intellectually (SAVI) approach which can be used to train the activeness and students' conceptual understanding. The development procedure is reference to the ADDIE development model. The research data were obtained in the form of validation data, readability data, response data, activeness data, and pretest posttest scores. The results showed that after going through the product validation process by material experts obtained an average percentage of 92,70% and included in the category of very feasible. Product validation by media experts obtained an average percentage of 82,39% and included in the very feasible category. The average readability gained 95,75% and included in the excellent category. The results of activeness obtained an average activity of students by 82,94% and included in the category of very active. The pretest and posttest showed an increase in students' conceptual understanding. The classical calculation state that at the pretest the concept understands is 37,27% while at the posttest is 63,59%. The average questionnaire responses for the use of Ludo-science media with SAVI received an average of 86,79% and included in the excellent category.